Warisan Budaya Leluhur Desa Sapit Zaman Pra Aksara yang Menjadi Identitas Masyarakat Lombok - Supiarmo, M. Gunawan; Jannata, Jannata; Amrina, Lisa; Harmonika, Sri; Alpionita, Resi; Indriani, Lilik; Hidayat, Asbur (Humanis; Vol 26 No 2 (2022), 2022)
Sapit is a village that is rich in natural resources and in the hospitality of its people. This village is also rich in cultural heritage in the form of relics of the pre-literate era, or the period before writing. The purpose of this study is to reveal information related to the pre-literate heritage of Sapit village as evidence of the identity of the Lombok people. This research uses a descriptive qualitative method, which is carried out through the data collection stage, including observation, interviews, and documentation. Furthermore, the data analysis techniques in this study are data collection, data reduction, and data presentation, as well as drawing conclusions about the cultural heritage of the pre-literate Sapit village. The results showed that Sapit village has a wealth of cultural heritage in the form of pre-literate relics, including dolmens, sarcophagi, punden, beads, menhirs, stone lisung, and statues